The effectiveness of note-taking and mutual responding strategies in developing literary analysis skills among tenth grade students - Abdullah, lulav; Nabi, Molod (Humanities Journal of University of Zakho, 2023)
The aim of the research is to identify the effectiveness of the strategies of note taking and mutually responding in developing literary analysis skills among tenth grade students, the researchers depended on the experimental group design for equal scores for the pre-test and post-test. The research community included tenth grade students in the secondary/intermediate schools for girls in the Directorate of Western Education affiliated to the General Directorate of Education in Duhok Governorate, average is (673) female students, for the academic year (2021-2022). The researchers deliberately chose (Hasar and Shahd Mullah Amin) schools for girls, and randomly chose (Hasar Secondary) for the experimental groups (18) students for the first group (23) students for the second group, and the (Shahid Mulla Amin Secondary) for the control group (22) students. The first experimental groups follow the note-taking strategy, and the second experimental group follows the strategy of the respondent, while the control group depended on the normal way. The researchers prepared a list of literary analysis skills, which included (6) basic skills, including each main skill modified from the second skills, which is (20) skills. The researchers prepared and tested those aforementioned skills, the skills of the literary analysis, as it included (40) paragraphs of the type of choice of moderation. And after completing the experiment, applying a test, extracting the data and conducting a statistical finding by using variance analysis (One way ANOVA) and (Scheffe test). The results showed that there is a strategically influence of the strategies of taking notes and responding mutually in developing literary analysis skills for the students of the two experimental groups.